PREDIKSI LOKASI RAWAN PEMBENDUNGAN ALAMI PADA DAERAH ALIRAN SUNGAI SEBAGAI MITIGASI BENCANA BANJIR BANDANG (DAS KRUENG TEUNGKU-KECAMATAN SEULIMUM-ACEH BESAR-PROVINSI ACEH) - Dirwan Dirwan; Azmeri Azmeri; Amir Fauzi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2013)
Flash floods have repeatedly occurred in Aceh province and happened at Seulimum Aceh Besar district on January 2, 2013. The flash floods flows to Krueng Raya and crashing Beureuneut village. Flash floods caused 90 % of the 90 houses in the village were submerged with a height varying between 1-3 meters. It is the repeat disaster. In 1980 a similar disaster has also resulted in a loss of community life. But until now there hasn’t been the availability of early warning systems particularly describing the the upstream of sub-watershed Krueng Tengku. Therefore this study aimed to evaluate volume of the natural damming. The results obtained is based on surface geological conditions in the upstream and downstream of the sub-watershed map of Krueng Tengku (SIMDAS KEMENHUT, 2012) and clarified through the maps of Google Earth Pro, field surveys, reflecting there are 2 (two) the natural dammings potential flooding flash if the collapse of a natural dam. Based on the soilcondition, land slope, land cover, then the condition that there is potential for containment dam collapse. Extensive analysis of the volume and surface damming through maps withdifference elevation of 1 meters+202 m to +210 m MSL. The maximum volume of natural damming 29.175.347,31 m3 and area of 3.160.747,69 m2(location I). Extensive analysis of the volume and surface damming through maps withdifference elevation of 2 meters+114 m to +122 m MSL. The maximum volume of natural damming 909,841.19 m3 and area of 282,048.36 m2(location II). Extensive damming of providing a very high hazard potential in the event of a dam collapse